-34=2(u-7)-7u

Simple and best practice solution for -34=2(u-7)-7u equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -34=2(u-7)-7u equation:



-34=2(u-7)-7u
We move all terms to the left:
-34-(2(u-7)-7u)=0
We calculate terms in parentheses: -(2(u-7)-7u), so:
2(u-7)-7u
We add all the numbers together, and all the variables
-7u+2(u-7)
We multiply parentheses
-7u+2u-14
We add all the numbers together, and all the variables
-5u-14
Back to the equation:
-(-5u-14)
We get rid of parentheses
5u+14-34=0
We add all the numbers together, and all the variables
5u-20=0
We move all terms containing u to the left, all other terms to the right
5u=20
u=20/5
u=4

See similar equations:

| x(3x-1)=-80 | | 7m=m-12 | | 18=10+2c | | 5x+6=2x+3+4x | | P+5x=6 | | 2/3x−24=1/6x−6 | | -3p-12=5p+60 | | 10(2n+1)+8(n+4)=8+8n+3n | | 5p+1-5p=-2 | | 2x+(-x)+2=3(-3)+10 | | 69+7x-1=90 | | e/12=3 | | 23x−24=16x−6 | | 3(6-c)=24 | | (5x-1)+(8x+14)=180 | | 4(u-8-7u=-26 | | -60x+21+-15x+9=180 | | .25x=3x-44 | | r+6.2/2=-2.6 | | 10(2n+1)+8(n+4)=8=11n | | 84×253g=352 | | 72=6(c-74) | | −4x−3(−3−4x)+5=2(2+4x) | | 2(4+15v)=-3(-10v-6) | | -2-0.5h+12=0.3h+6.2 | | 2x+3+3x=x+x+12 | | 12k+76=51 | | -6x-8+2x=12 | | 45637994167×7518904279942146098634g=13789 | | 7t+16=51 | | 3x+30=-7x-20 | | w/2-10=-2 |

Equations solver categories